Automation of productive machinery. Bases for an innovative business model - (:unkn) unknown (IEEE, 2024)
Nowadays, some laboratories perform elastic properties tests for concrete or rock cores using equipment manufactured 50 years ago. The original data collection procedure uses analog and manual recordings, which can cause inaccuracies in the measurements ...
Keywords: Automatización industrial; Modelo de negocio